SOME SOLUTIONS TO ATTRACT LEARNERS TO STUDY AT HUNG YEN UNIVERSITY OF TECHNOLOGY AND EDUCATION - Luong Thi Hai Yen; Hoang Thi Hong Dao; Hoang Minh Duc (Journal of Applied Science and Technology, 2019)
Recently, the number of universities and colleges in Vietnam is increasing significantly; on the contrary, the number of high school graduates tends to decrease. Therefore, universities, especially newly established universities, must improve their competitiveness to compete with top-notch universities to attract students. In this article, the author has analyzed the measures that Hung Yen University of Technical Education has implemented to attract learners to study at the school and also proposed some solutions to attract learners study at the school in the current period such as improving the quality of training, branding, communication enhancement; upgrade infrastructure for training, etc.